2014
DOI: 10.4037/ajcc2014484
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Perceptions of Family Presence during Resuscitation

Abstract: Background Although strong evidence indicates that the presence of a patient's family during resuscitation has a positive effect on the family, the practice is still controversial and is not consistently implemented. Objectives To explore nurses' experience with resuscitation, perceptions of the benefits and risks of having a patient's family members present, and self-confidence in having family presence at their workplace. Differences in demographic characteristics and relationships between nurses' perception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
50
2
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 9 publications
(17 reference statements)
7
50
2
8
Order By: Relevance
“…Yet, recent research continues to demonstrate unfavorable or mixed views of FPDR (9) 32 (94) 0 (0) 1 (3) 2 (6) 1 (3) 1 (3) 0 (0) 12 (35) 6 (18) 8 (24) 7 (21) 1 (3) 3 (9) 3 (9) 18 (53) 9 (26) 1 (3) 1 (3) 3 (9) 11 (32) 4 (12) 3 (9) 12 (35) 24 (71) 0 (0) 9 (26) 1 (3) 0 (0) 22 (65) 11 (32) 1 (3) 32 (94) 2 (6) 0 (0) 38 (95) 2 (5) 34 (85) 3 (8) 2 (5) 1 (2) 0 (0) 1 (2) 0 (0) 8 (20) 9 (22) 11 (28) 11 (28) 1 (3) 1 (2) 12 (30) 18 (45) 8 (21) 1 (2) 0 ( www.ajcconline.org among nurses. 2,26 Consequently, the need for creation of policies and programs and an increase in education 1,29,44,45 to facilitate acceptance and implementation of FPDR continues to be emphasized. Yet, among our total sample of critical care nurses who are frequently exposed to resuscitative care, we found that only 29.7% worked in a facility or unit that had an FPDR policy and only 41.9% had received any prior education on FPDR.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Yet, recent research continues to demonstrate unfavorable or mixed views of FPDR (9) 32 (94) 0 (0) 1 (3) 2 (6) 1 (3) 1 (3) 0 (0) 12 (35) 6 (18) 8 (24) 7 (21) 1 (3) 3 (9) 3 (9) 18 (53) 9 (26) 1 (3) 1 (3) 3 (9) 11 (32) 4 (12) 3 (9) 12 (35) 24 (71) 0 (0) 9 (26) 1 (3) 0 (0) 22 (65) 11 (32) 1 (3) 32 (94) 2 (6) 0 (0) 38 (95) 2 (5) 34 (85) 3 (8) 2 (5) 1 (2) 0 (0) 1 (2) 0 (0) 8 (20) 9 (22) 11 (28) 11 (28) 1 (3) 1 (2) 12 (30) 18 (45) 8 (21) 1 (2) 0 ( www.ajcconline.org among nurses. 2,26 Consequently, the need for creation of policies and programs and an increase in education 1,29,44,45 to facilitate acceptance and implementation of FPDR continues to be emphasized. Yet, among our total sample of critical care nurses who are frequently exposed to resuscitative care, we found that only 29.7% worked in a facility or unit that had an FPDR policy and only 41.9% had received any prior education on FPDR.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…25 Research has repeatedly shown that nurses are not uniformly supportive of FPDR with adult patients, 2,26-28 and thus FPDR is not commonly implemented at the bedside. In fact, only approximately one-third of nurses from across practice settings implement FPDR in their bedside care, 2,27,28 and recent research suggests an even lower implementation rate in critical care, 26 despite frequent opportunities for implementation owing to the fact that 45% of in-hospital cardiac arrests occur in a critical care setting. 17 Without nursing support, it is highly likely that FPDR will not be implemented and family-centered care will not be upheld.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Although the evidence for its positive effects on patients' families continues to increase, the practice is still under debate and its implementation remains inconsistent. 102,103 Using a 63-item survey, Tudor et al 104 conducted a monocentric study among a convenience sample of 154 nurses working in both inpatient and outpatient units to explore their experiences with resuscitation, perceptions of benefits and risks of family presence, and self-confidence in family presence at the workplace. The latter was significantly related (P < .001) to the perceived benefits, and was significantly greater in participants who had completed an advanced training program, were highly experienced in resuscitation, specialty certified, or a member of a professional organization.…”
Section: Family Mattersmentioning
confidence: 99%